2018
DOI: 10.1063/1.5050174
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of asymmetrical hysteresis phenomena observed in TMD-based field effect transistors

Abstract: To realize field effect transistors with multi-layered MoS2 and WSe2 (hereafter denoted as MoS2 FET and WSe2 FET), many device instability problems should be surmounted, such as the hysteresis generation of the devices. In order to clarify the mechanism of the asymmetrical hysteresis phenomena observed in the transfer characteristics of the MoS2 and WSe2 FET, the temperature dependencies of their characteristics are analyzed. Based on these analyses, it can be concluded that donor-like traps present in both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…There are positive charges on the top surface of CIPS, which attracts electrons of CIPS to the interface region to screen the positive polarization charges, resulting in an increase in the hole carrier density of WSe 2 and a decrease in the resistance . It is interesting to find that the electron branch also shows a clockwise hysteresis loop, which is probably because of the electron detrapping from the acceptor-like traps of the WSe 2 flake, as shown in Figure S9 …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…There are positive charges on the top surface of CIPS, which attracts electrons of CIPS to the interface region to screen the positive polarization charges, resulting in an increase in the hole carrier density of WSe 2 and a decrease in the resistance . It is interesting to find that the electron branch also shows a clockwise hysteresis loop, which is probably because of the electron detrapping from the acceptor-like traps of the WSe 2 flake, as shown in Figure S9 …”
Section: Resultsmentioning
confidence: 96%
“…9 It is interesting to find that the electron branch also shows a clockwise hysteresis loop, which is probably because of the electron detrapping from the acceptor-like traps of the WSe 2 flake, as shown in Figure S9. 35 The endurance and retention characteristics of the device were next examined to evaluate the reliability of the device in nonvolatile memory applications. As shown in Figure 4a, the amplitude of the periodic pulse was set to 6 V, the width of the pulse was set to 1 s, and the reading voltage was set to −2 V. We found that the programming (P) and erasing (E) states changed periodically with the pulse voltage shown in Figure 4b, with the P/E ratio greater than 10 3 when V d = 0.1 V. As shown in Figure 4c, the P/E ratio had no noticeable change after 100 cycles, indicative of the device's good antifatigue performance.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[ 27,28 ] These defects might originate from oxygen vacancies in the oxide, or sulfur vacancies in the MoS 2 , or water molecules that interact with the semiconductor. [ 29,30 ] Figure 1d shows the I D – V DS characteristics at increasing V GS at relatively small V DS from −100 mV to +100 mV. The linearity of the curves indicates ohmic‐like contacts between Ag and MoS 2 .…”
Section: Device Characteristicsmentioning
confidence: 99%
“…The structural specificity produces superior electrical and optical properties, and induces a sharp contact condition with other materials [52,53]. Moreover, because of their excellent mechanical properties such as flexibility and rigidity, 2D materials have attracted a lot of attention as potential candidates for various applications such as field-effect transistors (FET) [54,55], gas sensors [56], photo sensors [57,58] and flexible or ubiquitous substrates [59,60]. The information of electrical properties and structure dimension of 2D TMD materials was tabulated in Table 1.…”
Section: Two-dimensional Transition Metal Dichalcogenides Materialsmentioning
confidence: 99%